Cannabis use, schizotypy, and negative priming. Issue 3 (30th August 2015) - Albertella, Lucy; Le Pelley, Mike E.; Copeland, Jan
Abstract: The present study examined the effects of frequency of cannabis use, schizotypy, and age on cognitive control, as measured using a location-based negative priming task in a sample of 124 Australians aged 15–24 who had ever used cannabis. This study found that the schizotypy dimension of Impulsive Nonconformity had a significant effect on negative priming such that participants with higher scores on this dimension showed reduced negative priming. Also, higher levels of psychological distress were associated with greater negative priming. Finally, there was a significant age by cannabis use interaction indicating that younger, frequent users of cannabis may be more susceptible to its effects on cognitive control and perhaps at greater risk of developing a disorder on the psychosis dimension. Highlights: We used location-based negative priming as a measure of cognitive control. Higher levels of impulsivity were associated with reduced cognitive control. Higher levels of psychological distress were associated with greater cognitive control. Younger age was associated with reduced cognitive control among frequent cannabis users.